CHARACTER BUILDING THROUGH HADITH PERSPECTIVE (STUDY ANALYSIS ABOUT HADITH IMAN, ISLAM, AND IHSAN) - Ahmad, La Ode Ismail; Amri, Muhammad; Mosiba, Risna (Jurnal Diskursus Islam, 2019)
Character building is seen to be an essential answer of the grim value of education in which the gap is occured between intelectual intelligence and social intelligence. On the intelectual intelligence side, education system succesfuly delivers brilliant people. Meanwhile, on the social intelligence, some of those who are educated regarded the education as a showcase to justify actions that actually adverse the commonsense. This is, of course, go against the true value of eduction in which the outcome is to shape a brilliant, well-mannered generation. This is also compatible with the mission of Prophet Muhammad who aimed to complete the morality of human being. Therefore, teachers as the primary key of education bear a huge responsibilites to transfer all the knowledge to the learners according to Iman, Islam, and Ihsan philosophy. All can be done as the teachers become role models of Iman (faith), Islam (religious), and Ihsan (good behaviour) to their pupils in their learning process